2018
DOI: 10.1002/oby.22332
|View full text |Cite
|
Sign up to set email alerts
|

Examining Endocrine Disruptors Measured in Newborn Dried Blood Spots and Early Childhood Growth in a Prospective Cohort

Abstract: Objective: To determine whether newborn concentrations of perfluorooctane sulfonic acid (PFOS), perfluorooctanoic acid (PFOA), and bisphenol A (BPA) are associated with early childhood growth. Methods: We included 1954 singletons and 966 twins from the Upstate KIDS Study (born 2008–2010) with newborn dried blood spot concentrations of PFOS, PFOA and BPA quantified by liquid chromatography tandem mass spectrometry. Children’s weight and height were reported from birth through 3 years of age. Repeated measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…99% DF for PFOS and 90% for BPA Used DBS assay developed by Ma et al (2013) [ 86 ] Ghassabian 2018 [ 96 ] PFOS, PFOA, BPA 788 NDBS samples (Upstate KIDS study, 2008–2010) Longitudinal birth cohort study Elevated PFOS related to behavioral difficulties; elevated PFOA related to difficulties in prosocial behavior. PFOS and PFOA had DF of 100% Used DBS assay developed by Ma et al (2013) [ 86 ] Yeung 2019 [ 95 ] PFOS, PFOA, BPA 3111 NDBS samples (Upstate KIDS study, 2008–2010) Longitudinal birth cohort study PFOS and PFOA associated with lower BMI at 3 years of age; postnatal BPA exposure may occur in the hospital Used DBS assay developed by Ma et al (2013) [ 86 ] Robinson 2021 [ 97 ] PFOS, PFOA, epigenetic alterations 597 NDBS samples (Upstate KIDS study, 2008–2010) Cross-sectional High concentrations of PFOA/PFOS were not clearly associated with significant epigenetic alterations Used DBS assay developed by Ma et al (2013) [ 86 ] DNA was extracted from DBS samples Bell 2019 [ 97 ] PCBs, PBDE, p,p’-DDE 2065 NDBS samples (Upstate KIDS study, 2008–2010) Cross-sectional Elevated POPs were associated with an increased risk for large for gestational age and higher birth weight. >96% DF for DDE and many PCBs using pooled samples Used DBS methods developed by Ma et al (2014) [ 90 ] and Batterman and Chernyak (2014) [ 5 , 87 ] DBS samples pooled for analyses Gross 2020 [ 99 ] OCPs, PBDEs, PFASs 98 NDBS samples (Starting Early Program RCT) Nested case–control study >94% DF for most analytes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…99% DF for PFOS and 90% for BPA Used DBS assay developed by Ma et al (2013) [ 86 ] Ghassabian 2018 [ 96 ] PFOS, PFOA, BPA 788 NDBS samples (Upstate KIDS study, 2008–2010) Longitudinal birth cohort study Elevated PFOS related to behavioral difficulties; elevated PFOA related to difficulties in prosocial behavior. PFOS and PFOA had DF of 100% Used DBS assay developed by Ma et al (2013) [ 86 ] Yeung 2019 [ 95 ] PFOS, PFOA, BPA 3111 NDBS samples (Upstate KIDS study, 2008–2010) Longitudinal birth cohort study PFOS and PFOA associated with lower BMI at 3 years of age; postnatal BPA exposure may occur in the hospital Used DBS assay developed by Ma et al (2013) [ 86 ] Robinson 2021 [ 97 ] PFOS, PFOA, epigenetic alterations 597 NDBS samples (Upstate KIDS study, 2008–2010) Cross-sectional High concentrations of PFOA/PFOS were not clearly associated with significant epigenetic alterations Used DBS assay developed by Ma et al (2013) [ 86 ] DNA was extracted from DBS samples Bell 2019 [ 97 ] PCBs, PBDE, p,p’-DDE 2065 NDBS samples (Upstate KIDS study, 2008–2010) Cross-sectional Elevated POPs were associated with an increased risk for large for gestational age and higher birth weight. >96% DF for DDE and many PCBs using pooled samples Used DBS methods developed by Ma et al (2014) [ 90 ] and Batterman and Chernyak (2014) [ 5 , 87 ] DBS samples pooled for analyses Gross 2020 [ 99 ] OCPs, PBDEs, PFASs 98 NDBS samples (Starting Early Program RCT) Nested case–control study >94% DF for most analytes.…”
Section: Resultsmentioning
confidence: 99%
“…In another analysis of the same NDBS data ( n = 3111), Yeung et al analyzed the association between newborn exposure to these EDCs and early childhood growth patterns, including weight gain and obesity rates. PFOS and PFOA values were highly correlated ( R > 0.75) in NDBS samples from related twins; however, the association was lower for BPA ( R = 0.23) [ 95 ]. The study suggested that newborn exposure to BPA may occur through extended hospital stays in the neonatal intensive care unit [ 95 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential uses of DBS in environmental studies of pediatric cancer are extensive. Analytes of environmental exposures detectable in DBS reported to-date include benzene oxide, [15] lead, [16] mercury, [17] arsenic, [18] cadmium, [19] cotinine, [20,21] viral DNA, [22] organochlorine [23] and organophosphorus pesticides, [24] perfluorinated compounds, [25] polychlorinated biphenyls, [23] polybrominated diphenyl ethers, [26] bisphenol A, [25,27,28] phosphatidylethanol, [29] and polyfluoroalkyl chemicals. [30,31] Additionally, there is increasing awareness that epigenetic signatures of environmental exposures may provide effective biomarkers of past exposure.…”
Section: Novel or Underutilized Biospecimens In Environmental Studies Of Pediatric Cancer Using Dbs To Estimate Perinatal Exposuresmentioning
confidence: 99%
“…It can cross the placental barrier and is shown to be present in the cord blood at concentrations 1.5 to 3.5 times lower than those found in maternal blood. , In fact, this EDC is believed to be a cause of neonatal mortality, retarded postnatal growth, and delayed development. Moreover, the exposure of animals to PFOS during pregnancy, when associated with maternal stress, may lead to a decrease in motor function and delayed learning, depending on the sex of the offspring. PFOS is also associated with delays in eye opening and decreased viability in other developmental end points in rats and mice. …”
Section: Introductionmentioning
confidence: 99%